2018
DOI: 10.1016/j.conbuildmat.2018.07.134
|View full text |Cite
|
Sign up to set email alerts
|

Durability of new recycled granite quarry dust-bearing cements

Abstract: Imperative to the design of new cements that bear different types of waste as additions is a parallel study of the mechanical strength and durability of the new materials to ensure their performance will be satisfactory throughout their service life. This study explored the effect of adding 10 % or 20 % granite quarry dust to cement on properties such as transport (total and capillary water absorption and electrical resistivity), dimensional stability (drying shrinkage and expansion), the alkali-silica reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 60 publications
3
26
0
1
Order By: Relevance
“…As Table 4 also shows, total porosity rose with the ACMW replacement ratio: by approximately 7 % in ACMW20 and 29 % in ACMW50 samples relative to the reference. Figure 1 shows that the variations in total porosity were directly and linearly related to density, findings consistent with those reported by other authors using additions such as granite quarry dust [43] or marble [54]. The opposite pattern was observed for mean pore size (Table 4), which declined considerably with rising percentages of ACMW.…”
Section: 2density and Porositysupporting
confidence: 89%
“…As Table 4 also shows, total porosity rose with the ACMW replacement ratio: by approximately 7 % in ACMW20 and 29 % in ACMW50 samples relative to the reference. Figure 1 shows that the variations in total porosity were directly and linearly related to density, findings consistent with those reported by other authors using additions such as granite quarry dust [43] or marble [54]. The opposite pattern was observed for mean pore size (Table 4), which declined considerably with rising percentages of ACMW.…”
Section: 2density and Porositysupporting
confidence: 89%
“…In addition, they concluded that granite sludge may be effectively used in concrete bricks, paving units, and cement tiles' production. An enhanced durability of concrete incorporating granite sludge was also demonstrated in the study conducted by Medina et al [13], in 2018, with aesthetically sensitive applications. Vazzoler et al [14], in 2018, investigated the microstructural characteristics of paste produced with ornamental stone processing waste after heat treatment showing low pozzolanic activity, resulting in a denser final product due to the filler effect and a probable small pozzolanic reaction.…”
Section: Introductionmentioning
confidence: 52%
“…Quarry fines have been proven to be effective in mitigating the early decreasing of strength due to fly ash application [22]. It was also found that the partial replacement of cement by granite quarry dust is beneficial in several aspects including good durable behavior, less drying shrinkage and expansion, lower possibility of early-age cracking, while keeping strength properties comparable [23]. When used as stabilizer, quarry waste could improve the properties of soils in terms of better workability, a decrease in optimal water content and an increase in maximum dry unit weight [24,25], better swell and shrinkage properties for expansive soil [26], and satisfactory durability under freeze-thaw cycles [27].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Extended research attempts have been made to utilize quarry waste in constructions for both non-bearing [21,29] and structural purposes [20,22,23,29,30,31]. Non-bearing blocks made of quarry waste and other additives are common for wall partitions and decorations.…”
Section: Literature Reviewmentioning
confidence: 99%